Linguistic and cultural identity : Finns who have been through English immersion education - McCambridge, Laura (2007)
The aim of the study was to investigate the influence of English immersion education on the linguistic and cultural identities of Finns, with a view to understanding the interaction between English second language acquisition and identity. In-depth, semi- structured interviews were conducted with seven graduates from the English School in Helsinki, all of whom have Finnish parents and studied through English for most of their childhoods. The study addresses the question of whether acquiring and speaking English as children causes Finns to identify with non-Finnish linguistic and cultural communities, such as native English speaking communities. This is particularly relevant considering the growing use of English in Finland and the role of English as an international language.